Mouse model for exoerythrocytic stages of Plasmodium falciparum malaria parasite. - Sacci, J B (1992)
Research on the exoerythrocytic (EE) stages of human malaria parasites has been hindered because of the lack of an easily available suitable animal model. We report here an approach to produce mature EE-stage Plasmodium falciparum parasites by using severe combined immunodeficient (scid) mice with transplanted human hepatocytes. Transplantation of human hepatocytes into scid mice (scid hu-hep), their subsequent intravenous infection with P. falciparum sporozoites, and the development of mature liver-stage merozoites was achieved. Immunofluorescent staining of scid hu-hep kidney tissue sections demonstrated the presence of circumsporozoite protein (early during infection), merozoite surface antigen 1, and liver schizont antigen 1. The scid hu-hep model can serve as a source of human malaria liver-stage parasites, decreasing the need for nonhuman primates. Use of this model will facilitate characterization of EE-stage antigens and the assessment of stage-specific chemotherapeutic agents and candidate vaccines.